Evaluation of Monolayer and Bilayer Buccal Films Containing Metoclopramide - Blaž Grilc; Odon Planinšek (Pharmaceutics, 2024)
The objective of this study was to develop buccal film formulations containing metoclopramide hydrochloride monohydrate (MCP) with and without a backing layer and to evaluate their release properties and physiochemical stability. The crystallization of MCP in the polymer matrix was monitored with image analysis techniques for rapid and scalable observation. The results showed that the addition of a protective layer and its thickness significantly affected the release rate and crystallization behavior of MCP in the formulations. The crystallization of MCP increased over time, and certain formulations showed higher susceptibility to crystallization. To understand the factors affecting the crystallization of MCP, the relationship between the viscosity and pH of the casting solution was examined, but no significant correlation was found. A significant correlation was observed between the plasticizer concentration and the physical state of MCP. Through a systematic Design of Experiment (DOE) approach, an optimal formulation was devised, successfully preventing crystallization of the active ingredient. However, enhancing the overall chemical stability of the formulated product remains a challenge.